Effect of Embedment and Spacing Ratios on the Response of Lateral Load of Single and Group Piles - Mohammed Al-Neami; Mohammed Al-Dahlaki; Aya Chalob (Engineering and Technology Journal, 2021)
This paper displays an experimental work of three-scale model tests of single pile and nine–scale model tests of group pile (1x2) with spacing to diameter (S/D) ratios (2,4, and 6) respectively. The pile models inserted in the medium-dense dry sand with a relative density of 60% and different length to diameter (L/D) ratios (15, 25, and 30) were subjected to the lateral load with a rate of 2.5 mm/min. The test results present the effect of the change of the ratio of (L/D) and (S/D) on lateral displacements at the head of the pile. For single and group piles when the embedment ratio (L/D) increases, the ultimate lateral load increases also for group piles.When the (S/D) ratio increases, the ultimate lateral load increases. However, for (L/D) equal to 20, this increment is not linear with spacing increment, where a slight increment is observed of the relatively close pile and vice versa. While for other (L/D) ratios the increment of pile load is increased linearly with spacing increase.